Motivasi Peserta Pelatihan Instruktur Senam Aerobik Level 2 Di LKP Griya Dina Kabupaten Demak Jawa Tengah - Asiska Doni Oktafiyanto; Donny Anhar Fahmi (YLPK Mahardhika, 2021)
This research was motivated by the researcher's anxiety about the motivation of the training participants of level 2 aerobics instructor training which was caused by the researcher's doubts about the motivation of the participants of the level 2 aerobic exercise instructor training at LKP Griya Dina, Demak Regency. The purpose of this study was to determine the intrinsic motivation and extrinsic motivation of the training participants of level 2 aerobics instructor at LKP Griya Dina, Demak Regency. The researcher used a descriptive qualitative approach. The research location is LKP Griya Dina, Demak Regency. The informants in this study were the Chairperson, Administrators, LKP Griya Dina instructor trainers, and training participants for level 2 aerobics instructors. Data collection techniques in this study used several techniques, namely observation, interviews, and documentation. The data validity technique in this research is data triangulation. The analysis was carried out using a descriptive analysis model. The purpose of this study was to determine the intrinsic motivation and extrinsic motivation of the training participants of level 2 aerobics instructor at LKP Griya Dina, Demak Regency. The results showed that the trainees had an internal drive or intrinsic motivation as well as an external drive or extrinsic motivation that encouraged participants to attend level 2 aerobic exercise instructor training at LKP Griya Dina, Demak Regency. Regarding the participants' interest in becoming an aerobics instructor in Demak Regency, the researchers received an answer from the results of interviews with training participants that the trainees were also interested in becoming an aerobics instructor in Demak Regency.